2010
DOI: 10.1352/1944-7558-115.4.307
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder in Children and Adolescents With Fragile X Syndrome: Within-Syndrome Differences and Age-Related Changes

Abstract: The Autism Diagnostic Interview-Revised was used to examine diagnostic profiles and age-related changes in autism symptoms for a group of verbal children and adolescents with FXS, with and without autism. After controlling for nonverbal IQ, statistically significant between-group differences for lifetime and current autism symptoms were found for the Communication and Restricted Interests/Repetitive Behaviors domains, but not the Reciprocal Social Interaction domain. Effect sizes for differences in Reciprocal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
105
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 66 publications
9
105
3
Order By: Relevance
“…Previous studies have demonstrated significant associations between autism symptom severity, nonverbal cognitive ability, and FMRP in individuals with FXS. However, the correlations between FMRP and autism symptom severity often do not remain after controlling for differences in nonverbal IQ (e.g., Hatton et al, 2006;Kover et al, 2013;McDuffie et al, 2010;Thurman, McDuffie, Kover, Hagerman, & Abbeduto, 2015). Thus, given that our models of noncomprehension ability included both FMRP and nonverbal cognitive ability and the fact that nonverbal IQ seems to play a role in the presence of ASD symptomatology in FXS, it may not be surprising that autism symptomatology failed to emerge as a significant predictor.…”
Section: Noncomprehension Signaling In Boys With Fxsmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have demonstrated significant associations between autism symptom severity, nonverbal cognitive ability, and FMRP in individuals with FXS. However, the correlations between FMRP and autism symptom severity often do not remain after controlling for differences in nonverbal IQ (e.g., Hatton et al, 2006;Kover et al, 2013;McDuffie et al, 2010;Thurman, McDuffie, Kover, Hagerman, & Abbeduto, 2015). Thus, given that our models of noncomprehension ability included both FMRP and nonverbal cognitive ability and the fact that nonverbal IQ seems to play a role in the presence of ASD symptomatology in FXS, it may not be surprising that autism symptomatology failed to emerge as a significant predictor.…”
Section: Noncomprehension Signaling In Boys With Fxsmentioning
confidence: 90%
“…All participants were drawn from a larger project focused on the language and communicative development of children and adolescents with FXS or Down syndrome relative to younger TD children. Findings in this project have been reported in several publications Kover, Pierpont, Kim, Brown, & Abbeduto, 2013;McDuffie et al, 2010;McDuffie, Kover, Abbeduto, Lewis, & Brown, 2012;Oakes, Kover, & Abbeduto, 2013;Pierpont, Richmond, Abbeduto, Kover, & Brown, 2011), but none have focused on measures of noncomprehension signaling. Families were recruited by advertisements in local newspapers, mailings to local educators and administrators of genetic clinics, notices to families enrolled in a university research registry, postings on Internet website and listservs, and announcements in the newsletters of national organizations focused on developmental disabilities.…”
Section: Participantsmentioning
confidence: 99%
“…expressive language abilities compared with individuals having FXS alone (45). Most individuals with FXS and ASD have, in addition to the described hand mannerisms and speech problems, significant deficits in social interaction and communication persistently over time (46).…”
Section: Figurementioning
confidence: 99%
“…The prevalence of autism in FXS is estimated between 25% and 50% (see McDuffie et al, 2010), and is often an indicator of greater delays in communication and language (Abbeduto et al, 2007;Lewis et al, 2006;Philofsky, Hepburn, Hayes, Hagerman, & Rogers, 2004;Roberts, Mirrett, & Burchinal, 2001;Warren, Brady, Sterling, Fleming, & Marquis, 2010). However, several studies have reported no distinct language profiles between individuals with comorbid FXS and autism and individuals with FXS only, particularly in areas of expressive language, such as morphosyntax (Estigarribia et al, 2011;Lewis et al, 2006;Price et al, 2008), lexical diversity, talkativeness, and dysfluency .…”
Section: Factors Related To Language Development In Fxsmentioning
confidence: 99%